Tranexamic Acid Decreases Blood Transfusion Burden in Open Craniosynostosis Surgery Without Operative Compromise. Issue 1 (January 2019) - Lu, Victor M.; Goyal, Anshit; Daniels, David J.
Abstract : Abstract: In the surgical management of craniosynostosis, there is a high red blood cell (RBC) transfusion burden due to the small blood volume of the patients combined with significant blood loss that can occur with open surgery (OS). Tranexamic acid (TXA) is an antifibrinolytic which has been shown to decrease such a burden in particular surgeries. The aim of this study was to compare the operative outcomes of craniosynostosis OS which did and did not utilize TXA. Searches of 7 electronic databases from inception to February 2018 were conducted following Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. There were 206 articles screened against selection criteria for inclusion. Relevant data were extracted and analyzed using meta-analysis of proportions. A total of 9 comparative studies were included for meta-analysis. Compared with the control cohort, craniosynostosis OS utilizing TXA demonstrated significantly lower intraoperative RBC transfusion volumes (mean difference, −8.25 mL/kg; P < 0.001), blood loss (mean difference, −10.96 mL/kg; P < 0.001) and postoperative RBC transfusion incidence (odds ratio, OR, 0.12; P = 0.005). Fresh frozen plasma and crystalloid transfusion, operation time, length of stay, and complications were not significantly different with TXA use. Based on the comparative evidence currently available, TXA significantly decreased RBC transfusion burden during craniosynostosis OS without operative compromise. There is significant heterogeneity in reported TXA regimes in the literature. Future studies that are larger, randomized, and account for these factors will further enhance the authors' understanding. Abstract : Supplemental Digital Content is available in the text